2009
DOI: 10.1002/dvdy.21834
|View full text |Cite
|
Sign up to set email alerts
|

Small interfering peptide (siP) for in vivo examination of the developing lung interactonome

Abstract: To understand the role of reactive oxygen species in mechanosensory control of lung development a new approach to interfere with protein-protein interactions by means of a short interacting peptide was developed. This technology was used in the developing rodent lung to examine the role of NADPH oxidase (NOX), casein kinase 2 (CK2), and the cystic fibrosis transmembrane conductance regulator (CFTR) in stretch-induced differentiation. Interactions between these molecules was targeted in an in utero system with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Hence, F508delCFTR carriers must have accrued a sustained relative advantage in the cftr allelic race over millennia which suggests a function for F508delCFTR despite its recessive carriage (and presumed ER destruction). Given the dual importance of the F 508 region of CFTR [37,38] and CK2 in inflammation and host defence [39], and our recent finding that a tyrosine kinase linked to inflammation [SYK (spleen tyrosine kinase)] also controls CFTR in a CK2-interactive manner near the F 508 site [25], we have proposed that by adding (CFTR) peptide-induced miscontrol of CK2 to established models of CF pathogenesis, we might illuminate the complex path from the F508delCFTR defect to CF disease [24]. Thus the most pleiotropic protein kinase and an equivalently pleiotropic lethal recessive inherited disease of children could have a hidden relationship.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, F508delCFTR carriers must have accrued a sustained relative advantage in the cftr allelic race over millennia which suggests a function for F508delCFTR despite its recessive carriage (and presumed ER destruction). Given the dual importance of the F 508 region of CFTR [37,38] and CK2 in inflammation and host defence [39], and our recent finding that a tyrosine kinase linked to inflammation [SYK (spleen tyrosine kinase)] also controls CFTR in a CK2-interactive manner near the F 508 site [25], we have proposed that by adding (CFTR) peptide-induced miscontrol of CK2 to established models of CF pathogenesis, we might illuminate the complex path from the F508delCFTR defect to CF disease [24]. Thus the most pleiotropic protein kinase and an equivalently pleiotropic lethal recessive inherited disease of children could have a hidden relationship.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence is now available that the same CFTR peptides used in this in vitro study, when expressed by viral infection in a fetal animal model, do display biological effects, notably enhancement of Wnt reporter gene expression, which may well be mediated by CK2 [23]. Other caveats arise from the extremely variable dynamics of CFTR expression (and degradation), with peaks of 50-fold more mRNA found in fetal life compared with adult lung [52], leaving open the possibility that under special circumstances the proposed degraded peptide concentration might be higher than expected.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, peptides bearing the Phe 508 deletion (CFTRΔF508 peptides) were able to specifically inhibit CK2 α in a non-competitive manner with respect to a specific phosphoacceptor substrate. Recently, Cohen et al [23] described in vivo effects of these very same peptides in a developing lung model, such that Phe 508 -dependent changes in protein–protein interactions occur when such peptides are expressed using a peptide-encoding virus to infect the developing embryo. Importantly, in CF, the mechanism by which loss of Phe 508 induces a multi-system disease that destroys many organs remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Ferec and colleagues showed that the developing human fetus expresses CFTR very early in gestation and that the timing of this expression is disrupted by F508del‐CFTR mutation . This idea has been modelled in the developing fetal rat lung by Cohen and colleagues who virally overexpressed either sense or antisense constructs of CFTR and showed defects in cell signalling in lung smooth muscle cells and functional changes in the assembly of protein–protein contacts within the epithelial NADPH oxidase complex that mediates bacterial killing and inflammation . They observed that the oxidase subunit assembly was disrupted by expressing short peptides with sequence homology to the F508del region of CFTR.…”
Section: Embryologymentioning
confidence: 99%